TINJAUAN INDIKATOR EFISIENSI RUMAH SAKIT PADA RUANG RAWAT ANAK GUNA MENINGKATKAN MUTU PELAYANAN DI RUMAH SAKIT BHAYANGKARA TK. II SARTIKA ASIH BANDUNG - Trianto, Wowo; Abidin, Inal (Jurnal TEDC; Vol 19 No 2 (2025): JURNAL TEDCDO - 10.70428/tedc.v19i2.1260, 2025)
Based on the results of observations conducted in the Inpatient Pediatric Medical Record Reporting Room at Bhayangkara Tk.II Sartika Asih Hospital in Bandung, there are efficiency parameters for inpatient services that have not reached the ideal level. The Bed Occupancy Rate (BOR) does not meet the Barber Johnson standard, which should be between 75% and 85%. The purpose of this study is to determine the efficiency level of bed utilization in the Pediatric Ward in order to improve the quality of healthcare services. The research method used is descriptive with a qualitative approach, employing data collection techniques through interviews, observations, and document studies. Based on the research findings, it was revealed that in January and December there was an increase in BOR, Length of Stay (LOS), Turnover Interval (TOI), and Bed Turnover (BTO), which did not meet the Barber Johnson standard.